2006
DOI: 10.1111/j.1600-0897.2006.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmune and Autoimmune Background in Recurrent Pregnancy Loss – Successful Immunotherapy by Intravenous Immunoglobulin

Abstract: The novel cellular immunological assays proved to be favourable for the indication of RSA patients and showed the usefulness of this selection process for effective immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…However, many clinical studies where IVIG were given to women suffering from recurrent spontaneous abortions, a noninflammatory condition, reported the opposite results, ie, decreased NK cell cytolytic activity and/or decreased number or percentage of circulating NK cells in treated women [35][36][37][38][39][41][42][43][44]. These discrepancies could be explained by the various conditions in which IVIG are used and, particularly, the existence or not of an inflammatory state.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, many clinical studies where IVIG were given to women suffering from recurrent spontaneous abortions, a noninflammatory condition, reported the opposite results, ie, decreased NK cell cytolytic activity and/or decreased number or percentage of circulating NK cells in treated women [35][36][37][38][39][41][42][43][44]. These discrepancies could be explained by the various conditions in which IVIG are used and, particularly, the existence or not of an inflammatory state.…”
Section: Discussionmentioning
confidence: 77%
“…Until recently, the possible role of NK cells in mediating the immunomodulatory effect of IVIG had never been mentioned. On the contrary, it was suggested that for preventing miscarriage, IVIG could act by inhibiting NK cells [35][36][37][38][39][40][41][42][43][44]. However, very recently, Chong et al [45] elegantly demonstrated that NK cells are necessary for the prevention of experimental autoimmune encephalomyelitis (EAE) by IVIG treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Immunoglobulin therapy has been shown to be clinically beneficial in some selected groups of women with RPL by reducing NK cell cytotoxicity or favorably decreasing Th1/Th2 ratios (52)(53)(54). Our preliminary data revealed that the immunoglobulin therapy was effective for decreasing pregnancy loss in Sphk1…”
Section: Sphk2mentioning
confidence: 69%
“…This study revealed that RSA patient show high total capacity of iron bounding in peripheral blood and a HLA class I mismatch, a high cytotoxic potential that may be associated with the lack of erythrocytes antibody inhibition-blocking antibody, that appeared after IVIG therapy and were associated with the continuation of the pregnancies [93].…”
Section: Nk Cells and High Doses Intravenous Immunoglobulinsmentioning
confidence: 97%